Pengaruh Harga, Promosi, dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen pada Ice Cream Momoyo Cabang Rungkut Surabaya - Arnoldina; Rifda; M.Azizul K (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
This study aims to examine the influence of price, promotion, and product quality on consumer purchasing decisions at Ice Cream Momoyo, Rungkut Branch, Surabaya. The background of this research is based on the increasing competition in the modern beverage industry, particularly among Millennials and Generation Z, who serve as the target market. This research employs a quantitative approach with a survey method. Data were collected through the distribution of questionnaires to 100 respondents who had purchased and consumed Momoyo products. The sampling technique used was purposive sampling, and the sample size was determined using the Cochran formula. The data analysis technique applied is multiple linear regression with the assistance of SPSS version 23. The results show that the variables of price, promotion, and product quality have a positive and significant effect on purchasing decisions. Simultaneously, price, promotion, and product quality significantly influence purchasing decisions, with a coefficient of determination value of 82.1%.